Complementary and Alternative Medicine Use by Patients Chronically Infected with Hepatitis C Virus. (2007) - White, Colin P; Hirsch, Gerilynn; Patel, Sunil; Adams, Fatin; Peltekian, Kevork M
Abstract : Complementary and alternative medicine (CAM) is becoming increasingly popular in North America. The use of CAM is also popular in patients with chronic liver disease but is not well documented. The extent of use of CAM in chronic hepatitis C virus (HCV) infected patients was determined, and the demographic and clinical data between users and nonusers of CAM was compared. Seventy-six patients (30% female) with chronic HCV were interviewed. The mean age was 43±8 years. Current use of CAM for HCV was reported by 35 of 76 patients (46%). Eighteen of 76 patients within this group used herbal supplements (24%). The most commonly used herb was Silybum marianum (milk thistle), reported by 10 of 76 patients (13.2%). Commonly reported benefits of CAM use included reduction in fatigue, boost in the immune system and improved gastrointestinal function. No adverse effects of CAM use were reported. In the present study, four of 18 patients (22%) with chronic liver disease taking herbal therapies were on herbs that increased bleeding time. The use of CAM in chronic HCV patients is significant. Patients should be asked specifically about their use of CAM. CAM use may have implications affecting conventional treatment and management of HCV.